(3OQGSGJ GdLOhi GdGbJUGOjI hGdGLJeGYjI ddeTGQjY (B/s - (3OjGH, eMeOs ((3HjQhJ(B: s (3OGQ GdefGgd GddHfGfj(B, s, 2007)
(3jMJhj gPG GdcJGH Ydi eGjdj GdGSJKeGQ WHjYJg CgejJg hCgOGag, OQGSI GdLOhi GdGbJUGOjI ddeTGQjY, GdOQGSI GdbGfhfjI, GdOQGSI GdJShjbjI, OQGSI GdLOhi GdafjI, eUGOQ GdJehjd, eYjjQ Jbjje GdeTGQjY, eYjGQ GdbjeI GdMGdjI GdUGajI, eYjGQ eYOd GdYGFO GdOGNdj, Jbjje eYjGQj GdbjeI GdMGdjI GdUGajI, eYjGQ aJQI GdGSJQOGO(B/(3eYjGQ eYOd GdYGFO GdeMGSHjs
(3HjHdjhZQGajG U(B.277s
Keywords: (3GJNGP GdbQGQs; (3EOGQI CYeGds; (3GdeTQhYGJs; (3OQGSGJ GdLOhis